A review on recent advances in the fabrication and evaluation of superhydrophobic concrete. (15th May 2022) - Wu, Yuanlong; Dong, Lei; Shu, Xin; Yang, Yong; She, Wei; Ran, Qianping
Abstract: Water penetration can cause severe performance deterioration and even failure of concrete constructions through various degradation mechanisms, such as chemical erosion, dry-wet alternations, carbonation, freeze-thaw cycles, etc., which may result in safety concerns and tremendous economic loss. To address these issues, superhydrophobic concrete materials in the form of coating layer or monolith have received considerable attention in the past decade. In this review, the basic wettability models with the specific case of concrete are presented at first. Then, the reported advanced strategies for constructing superhydrophobic concrete are reviewed and categorized into superhydrophobic surface and bulk modification, and the advantages/disadvantages of the two distinct strategies are summarized. Besides, as concrete is the most important load-bearing component in construction, the influence of superhydrophobic modification on the mechanical properties of concrete is discussed. In addition, the commonly used durability performance evaluation criteria for superhydrophobic concrete materials, including water impermeability, corrosion resistance, anti-icing ability/freeze-thaw resistance, and ultraviolet (UV) resistance are comprehensively reviewed. Finally, the remaining challenges in the fabrication and application of high-performance superhydrophobic concrete and prospective solutions for addressing these problems are presented. Highlights: Superhydrophobic modification reduces the permeation of external water and thus enhances the durability of concrete. The various fabrication methods for superhydrophobic surface or bulk modification of concrete were reviewed and compared. The performance evaluations for superhydrophobic concrete were reviewed and future research priorities were concluded.